Moderate nitrogen application facilitates Bt cotton growth and suppresses population expansion of aphids (Aphis gossypii) by altering plant physiological characteristics - Guo, Lixiang; Niu, Lin; Zhu, Xiangzhen; Wang, Li; Zhang, Kaixin; Li, Dongyang; Elumalai, Punniyakotti; Gao, Xueke; Ji, Jichao; Cui, Jinjie; Luo, Junyu (Frontiers in Plant Science, 2024)
Excessive application of nitrogen fertilizer in cotton field causes soil and water pollution as well as significant increase of aphid population. Reasonable fertilization is an important approach to improve agricultural production efficiency and reduce agriculture-derived pollutions. This study was aimed to explore the effects of nitrogen fertilizer on the Bt cotton physiological characteristics and the growth and development of A. gossypii, a sap-sucking cotton pest. Five different levels of Ca(NO3)2 (0.0 g/kg, 0.3 g/kg, 0.9 g/kg, 2.7 g/kg and 8.1 g/kg) were applied into vermiculite as nitrogen fertilizer in order to explore the effects of nitrogen fertilizer on the growth and development of Bt cotton and aphids. The results showed that the medium level of nitrogen fertilizer (0.9 g/kg) effectively facilitated the growth of Bt cotton plant and suppressed the population expansion of aphids, whereas high and extremely high nitrogen application (2.7 and 8.1 g/kg) significantly increased the population size of aphids. Both high and low nitrogen application benefited aphid growth in multiple aspects such as prolonging nymph period and adult lifespan, enhancing fecundity, and improving adult survival rate by elevating soluble sugar content in host Bt cotton plants. Cotton leaf Bt toxin content in medium nitrogen group (0.9 g/kg) was significantly higher than that in high (2.7 and 8.1 g/kg) and low (0.3 g/kg) nitrogen groups, but Bt toxin content in aphids was very low in all the nitrogen treatment groups, suggesting that medium level (0.9 g/kg) might be the optimal nitrogen fertilizer treatment level for promoting cotton seedling growth and inhibiting aphids. Overall, this study provides insight into trophic interaction among nitrogen fertilizer levels, Bt cotton, and cotton aphid, and reveals the multiple effects of nitrogen fertilizer levels on growth and development of cotton and aphids. Our findings will contribute to the optimization of the integrated management of Bt cotton and cotton aphids under nitrogen fertilization.